Switched reluctance motor actuating systems for multirotor air vehicles - Biczyski, Marcin (Cranfield University, 2022)
Among the race to net zero emissions, new vehicle concepts are thriving. Multirotor air vehicles are popular for consumer-grade applications like sport or photography, but they are also considered to solve the challenges of Urban Air Mobility. By analysing the multirotor vehicles and their typical faults, the highest severity of faults is attributed to the actuating system, of which the central component is the electric motor. Comparing avail- able technologies, switched reluctance (SR) motors are deemed a promising solution due to their high degree of fault-tolerance, ruggedness, sustainability and the lack of permanent magnets. Therefore, this study presents a process of designing an SR motor actuating system for use in multirotor vehicle applications. The efforts are focused on achieving desired functionality and documenting technical challenges, rather than achieving an optimal design. A pre-study on multirotor vehicle sizing methodology based on databases of off-the- shelf components is presented. This is then expanded to cover systems with electric motors in general. Based on sizing specifications, a set of SR motors is optimised for a range of vehicle weights. One design (corresponding to 8 kg quadrotor vehicle) is chosen for further analysis and manufacture. A PI controller-based control solution is developed and implemented, along the model of the whole actuating system in a simulator. Simulated performance is compared with that of a reference BLDC motor actuating system. In addition, system behaviour is analysed in the presence of uncertainties and injected faults. Results are expressed in terms of Loss of Effectiveness (LOE) metric used for the development of fault-tolerant control. The SR motor actuating system is then verified to be of adequate performance and good fault-tolerance, especially against open circuit faults in one or two phases. However, the system was found to be susceptible to position sensing system failure. In a preliminary comparison with BLDC motor actuating systems, the designed system is comparable in terms of performance, advantageous in terms of fault-tolerance and of considerably higher weight, which is attributed to immaturity of the technology. Sources of the SR motor system advantages are identified as reluctance torque and separation of phases, and recommended for further study.
Keywords: Multirotor; UAV; Actuating system; Switched reluctance; Electric motor; Fault-tolerance; Reliability